The Human Gut Phageome: Origins and Roles in the Human Gut Microbiome - Townsend, Eleanor M.; Kelly, Lucy; Muscatt, George; Box, Joshua D.; Hargraves, Nicole; Lilley, Daniel; Jameson, Eleanor (Frontiers in Cellular and Infection Microbiology, 2021)
The investigation of the bacterial populations in the gut, known as the microbiome, has led to a revolutionary field of science, and understanding on the impacts on human development and health. Following these revelations about bacteria, other kingdoms of life, such as fungi, have been thoroughly researched. Trailing behind these is the interrogation of the gut virome, specifically the phageome. Bacteriophages, viruses that infect bacterial hosts, are known to dictate the dynamics and diversity of bacterial populations in a number of ecosystems. However, the phageome of the human gut, while of apparent importance, remains an area of many unknowns. In this paper we discuss the role of bacteriophages within the human gut microbiome. We examine the methods used to study bacteriophage populations and how this has evolved over time, leading to the answers, but also many questions, we have now about the phageome. We review the development of the phageome in infancy and factors that may influence the viral populations in adult life. The role and action of this phageome is then discussed at both a biological level, and in the broader context of human health and disease.